Classificação dos partos em um hospital terciário do Ceará baseada em características obstétricas das pacientes - Moura, Victor de Alencar (2018)
The number of cesarean sections is growing worldwide and, in Brazil, the cesarean rate in the public network is around 52%. This value is higher than the one recommended by the World Health Organization (WHO) that is 15%. The Ten-Group Robson Classification (SCRDG) is a classification based on the basic obstetric characteristics of the patients. The World Health Organization has recommended the use of the Robson Classification as a global standard classification for the evaluation, comparison, and monitoring of cesarean rates. Considering the importance of a basis for the indication of cesarean sections and the need of reducing the number of unnecessary caesarean sections, the goal of this study was to use the SCRDG to classify a group of women admitted to gave birth over July to December 2017 in the Maternidade Escola Assis Chateaubriand, which is a tertiary healthcare university hospital and a center of reference in maternal and neonatal care in the state of Ceará (Brazil). In this observational and cross-sectional study the data were collected in a standardized chart with information about the parity, obstetric history of cesarean section, onset of labor, fetal presentation, and gestational age at birth. The study considered a sample of 494 reports for vaginal deliveries and 795 reports for abdominal deliveries (55% of all deliveries performed for each category over the studied period). Data were managed using Microsoft Excel® spreadsheets. The Robson groups with the highest impact in the cesarean rate were Group 2 (20.66%), Group 5 (27.76%) and Group 10 (16.98%), which accounted for more than 65% of the cesarean sections performed during the evaluated period. The cesarean rate for the used sample was 62.05%, considering the evaluated period, which differed in only 1% from the value reported by the MEAC's Care Management Report (61.05%). A rate of 4.4% "unclassified reports" was obtained, which indicates that efforts should be made to correctly fill in the sheets, with the inclusion of all required data. The rate of vaginal delivery was 37.96% for the evaluated sample, which differed by 0.99% from the value reported by the MEAC's Care Management Report (38.95%). The groups with the highest impacts in the rate of vaginal delivery were groups 3 (35.70%), 1 (31.83%), and 10 (21.07%). Comparing the results obtained in this study with the ones obtained by other tertiary healthcare hospitals from Brazilian universities, one can observe that the Maternidade Escola Assis Chateaubriand follows the same trend in relation to the contribution of the Robson groups, but with the global cesarean rate somewhat higher (57.9%). Finally, it is concluded that the use of SCRDG is a powerful tool to analyze births and define where efforts should be focused to reduce the global cesarean rate in MEAC to the values considered ideal by the WHO.